2017
DOI: 10.1002/bdr2.1040
|View full text |Cite
|
Sign up to set email alerts
|

Plasma folate levels and associated factors in women planning to become pregnant in a population with high prevalence of neural tube defects

Abstract: Women who planned to become pregnant had very low plasma folate in the population. Folic acid supplementation was the only factor to be associated with a high plasma folate concentration. High NTD risk would remain if women would get pregnant without having taken folic acid supplements. Birth Defects Research 109:1039-1047, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
5
1
Order By: Relevance
“…Of particular importance, the findings that mean PF differed significantly between ethnic groups (with a significantly lower PF level observed in Pacific participants) warrants further exploration. A higher BMI category was also significantly negatively associated with PF in the present study, in contrast with the findings by Liu et al (45) and Ma et al (57) . This difference is probably due to the use of only two categories of BMI in their analyses (normal BMI v. overweight), whereas the present study also included a third (BMI >30 kg/m 2 (obese)) category.…”
Section: Discussioncontrasting
confidence: 99%
“…Of particular importance, the findings that mean PF differed significantly between ethnic groups (with a significantly lower PF level observed in Pacific participants) warrants further exploration. A higher BMI category was also significantly negatively associated with PF in the present study, in contrast with the findings by Liu et al (45) and Ma et al (57) . This difference is probably due to the use of only two categories of BMI in their analyses (normal BMI v. overweight), whereas the present study also included a third (BMI >30 kg/m 2 (obese)) category.…”
Section: Discussioncontrasting
confidence: 99%
“…The results were consistent with the previous studies [24,43,44]. Because the prevalence (19%) of 677TT genotype is high in China, the risk of exposure to plasma folate deficiency, resultant hyperhomocysteinemia, and adverse pregnancy outcome may elevate [45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…Besides, Chinese government recommends all of the childbearing age women consuming 0.4 mg folic acid daily, and the rate of NTDs has shown a declining trend [54][55][56]. However, compared with US women's plasma folate level, our data indicated that the plasma folate level was lower than the geometric mean 37.3 nmol/L [46,57]. In conclusion, as many pregnancies are unplanned, and taking the MTHFR C677T and MTRR A66G polymorphisms and environmental factors into account, we recommend that health providers supply appropriate folic acid with or without multiple vitamin supplements to all childbearing age women based on their genotypes and vitamin status.…”
Section: Discussionmentioning
confidence: 51%
“…None of the folate replete women recruited in the present study were taking folic acid supplements preconceptionally. On the contrary, a study on women from Northern China revealed that 50% of them who planned to become pregnant had very low plasma folate levels (Ma, Wang, Jin, Li, & Ren, ). A study on Korean women reported only 26.4% preconceptional use of folic acid (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%